A Comparison of Six Global Ranking Systems Considering Weight Distribution and Indicator Types by Correlation Analysis - Ghose, Sumita; Akhtar, Md. Yeosuf (Journal of Information and Knowledge, 2023)
The study examines and compares the indicators used by the six global ranking systems, as well as the weights assigned to the indicators used by each ranking system. In the comparison process, the inter-ranking correlation between the ranking systems is determined by Spearman’s rank correlation method to understand primarily the similarities between different ranking systems based on rank or positions held by different institutions. The study frames all the indicators, considering various ranking systems, in a common ranking framework for establishing the co-relation matrix. The framing of seven distinct ranking characteristics or indications aids in understanding the weighting scheme used by the six ranking methods. The work then further investigates the reasons for differing Spearman’s ranking correlation values by exploring different ways of calculating the ranking indices adopted by different ranking agencies. The weight distribution across the indicators is another factor which is required to be taken into consideration while observing the correlation between the two ranking systems. Karl Pearson’s statistical measure is applied to find the similarities of the weights associated with each indicator in different raking systems. The outcome of this research provides a comprehensive view of countries like India which are participating in different international ranking systems to improve their ranking while taking part in various ranking systems. Different test cases and in-depth analyses show that it is not an easy task for the institutes to perform better in all the ranking systems.